2020
DOI: 10.1007/s10495-020-01614-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic DNA sensing through cGAS and STING is inactivated by gene mutations in pangolins

Abstract: The release of DNA into the cytoplasm upon damage to the nucleus or during viral infection triggers an interferon-mediated defense response, inflammation and cell death. In human cells cytoplasmic DNA is sensed by cyclic GMP-AMP Synthase (cGAS) and Absent In Melanoma 2 (AIM2). Here, we report the identification of a "natural knockout" model of cGAS. Comparative genomics of phylogenetically diverse mammalian species showed that cGAS and its interaction partner Stimulator of Interferon Genes (STING) have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…These findings indicate that cow may be a putative intermediate host between pangolin and human, but this will require further investigation. While pangolins have been found to have unusual resistance against viral, including coronavirus, infection [ 41 , 42 ], the cow is also well known for its unusual antiviral responses, including those via neutralizing antibodies (“cattlebodies”), which are effective, for example, against retroviral infections such as HIV [ 43 ], and are also under investigation for their effectiveness against SARS-CoV-2. Coronaviruses are well known in cattle and can cause gastroenteritis, respiratory disease, winter dysentery and shipping fever pneumonia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that cow may be a putative intermediate host between pangolin and human, but this will require further investigation. While pangolins have been found to have unusual resistance against viral, including coronavirus, infection [ 41 , 42 ], the cow is also well known for its unusual antiviral responses, including those via neutralizing antibodies (“cattlebodies”), which are effective, for example, against retroviral infections such as HIV [ 43 ], and are also under investigation for their effectiveness against SARS-CoV-2. Coronaviruses are well known in cattle and can cause gastroenteritis, respiratory disease, winter dysentery and shipping fever pneumonia [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that cGAS knockout mice are healthy and normally developed in a barrier facility [ 60 ]. Furthermore, cytosolic DNA sensing through cGAS and STING is inactivated due to gene mutations in wild pangolins [ 61 ]. Thus, future works will be needed to use genetic tools to establish mouse cancer models in cGAS deficiency or PTM deficiency backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that some key genes related to immune function in the innate immune system of pangolins are pseudogenized or mutated, resulting in the loss of their immune pathways and functions involved in resistance to viral or bacterial invasion, and it is speculated that pangolins may have some undiscovered immune replacement compensation mechanisms 27 , 28 . However, we do not agree with some scholars who suggest that the evolution of pangolin scales is an innovative compensation for low immune function of the back skin 7 .…”
Section: Discussionmentioning
confidence: 99%